Dysmorphism and major anomalies are a main predictor of survival in newborns admitted to the neonatal intensive care unit in the Democratic Republic of Congo. Issue 2 (27th November 2020) - Mubungu, Gerrye; Makay, Prince; Lumaka, Aimé; Mvuama, Nono; Tshika, Dahlie; Tady, Bruno‐Paul; Biselele, Thérèse; Roelants, Mathieu; Tshilobo, Prosper Lukusa; Devriendt, Koenraad
Abstract: In Central‐Africa, neonatal infections, asphyxia and prematurity are main reasons for admission to the neonatal intensive care unit and major determinants of newborn survival. Also, the outcome of newborns with congenital anomalies is expected to be poor, due to a lack of state‐of‐the art care. We conducted a study of 102 newborns recruited in the Neonatal Intensive Care Unit (NICU) at the University Hospitals of Kinshasa, DR Congo, to assess the impact of congenital anomalies. The presence of a major anomaly was associated with a hazard ratio of death of 13.2 (95%CI: 3.7–46.7, p  < .001). In addition, the presence of three or more minor anomalies was associated with a 4.5‐fold increased risk of death (95%CI: 1.1–18.6, p = .04). We conclude that like major anomalies, the presence of three or more minor anomalies should also be given particular attention and that the evaluation of dysmorphism should be promoted in NICU.